TRADISI BUKA RANTAU LARANGAN DI DESA SEIKIJANG KECAMATAN ROKAN 1V KOTO KABUPATEN ROKAN HULU - Pitrawati '; Isjoni '; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: There are many traditions in Seikijang Village, one of them is open Rantau Larangan. Open Rantau Laranan is a tradition of ancestors who have come down from tens of years ago and continues to grow today. This activity is open once in two years. The purpose of this research is 1) to know the history of tradition open Rantau Prohibition Seikijang Village Rokan 1V Koto Rokan Hulu District, 2) To know the factors that encourage the community Seikijang in doing Tradition Open Rantau Larangan in the village Seikijang Rokan 1V Koto Rokan Hulu District, 3) To know the process of implementation of tradition Open Rantau Prohibition in the village Seikijang Rokan 1V Koto Sub-district Rokan Hulu, 4) To know the benefits of tradition Open Rantau Prohibition for community Seikijang Rokan 1V Koto District Rokan Hulu District. In this study using descriptive method, with a qualitative approach, where it will provide complete information so useful for science. The results of this study indicate that Open Rantau Larangan is a tradition that has existed since tens of years ago located in the village of Saikijang. There are several stages performed in the implementation of Open Prohibition Prohibition that is according to customary decisions, locking process, opening process, fishing gear facilities, process management results Open Rantau Prohibition. Has functions and contains values for people's lives.Keywords: Open Prohibition Track, Tradition